The effects of hypnosis on flow and putting performance in golfers - Dao, T. D. (2019)
Csikszentmihalyi (1975) introduced the flow concept, involving total absorption in the task, confidence, and control, with effortless, automatic movement. Flow has nine dimensions that Stavrou and Zervas (2004) divided into five antecedents (challenge-skill balance, clear goals, unambiguous feedback, total concentration on the task, sense of control) and four concomitant dimensions (action-awareness merging, loss of self-consciousness, time transformation, and autotelic experience). Loss of self-consciousness and time transformation have similarities to phenomena often reported in hypnotic trance states. To examine whether the experience of these phenomena in hypnosis enhanced flow state, I performed three studies. In Study 1, I evaluated whether a hypnotic state facilitates flow and enhances performance via its concomitant dimensions and whether the trancework component of traditional hypnosis (TH), compared with neutral hypnosis (NH), is crucial, with 20 golfers, who performed putting under controlled conditions. In Study 2, I examined the effect of two hypnosis techniques, regression (RE) and future progression (FP) on golf putting performance and flow state with 25 golfers. Both studies had the same structure. I used the Waterloo-Stanford Group C Scale of Hypnotic Susceptibility (WSGC) to match participants into conditions. Golfers performed 56 4m test putts at pre-test and post-test. I measured radial error of each putt and number of putts holed. Then they completed the Flow State Scale-2 (FSS-2) at pre- and post-test. All participants undertook a 60-minute, face-to-face session, then listened to a recording of that session for seven days with different hypnotic suggestions in the RE and FP conditions. In Study 1, two-way mixed-design ANOVA revealed that TH reduced radial error and two dimensions of flow, sense of control and loss of self-consciousness, compared with NH. In Study 2, two-way mixed design ANOVA showed that the effect of FP was significantly larger than the effect of RE in facilitating global flow mainly due to the time transformation dimension, but performance was not enhanced. In Study 3, I investigated the effect of FP on flow and putting performance in competitions. Three male golfers participated in a single-case design (SCD) study, comprising six competition rounds in the Baseline Phase (BP) and six rounds in the Intervention Phase (IP). I recorded number of putts per round, percentage distance error, strokes gained putting, global flow state, and flow dimensions. Visual inspection and split-middle technique analysis of individual graphs indicated improvement in performance and flow of two golfers. I used narrative analysis to examine social validation questionnaire responses. Participants reported superior performance with more confidence and greater concentration after the hypnosis intervention. The findings of these three studies indicate that RE and FP hypnosis can be useful techniques to promote flow and improve performance. Further study is warranted to identify the most effective combination of hypnosis techniques to enhance, global flow state, flow dimensions, and performance.